2020
DOI: 10.3390/cancers12113263
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone Treatment Promotes Testicular Leydig Cell Tumor Progression in Transgenic Mice

Abstract: The selective progesterone receptor modulator mifepristone (MF) may act as a potent antiproliferative agent in different steroid-dependent cancers due to its strong antagonistic effect on the nuclear progesterone receptor (PGR). Hereby, we analyzed the effects of MF treatment on Leydig cell tumor (LCT) progression in a transgenic mouse model (inhibin-α promoter-driven SV40 T-antigen), as well as on LCT (BLTK-1 and mLTC-1) cell proliferation. MF significantly stimulated the proliferation of LCT in vitro. Simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…The PGRMC2 protein also exhibited increased phosphorylation in the MA-10 Leydig cells treated with Fsk+AICAR vs. controls. PGRMC2 is a membrane-associated progesterone receptor (MAPR) present in Leydig cells and is believed to play a role in the progesterone auto/paracrine action on Leydig cells [ 55 , 56 ] in addition to potentially regulating the activity of some cytochrome P450 enzymes [ 57 ]. We showed that PGRMC2 is present in MA-10 Leydig cells and that it is phosphorylated after AMPK activation.…”
Section: Discussionmentioning
confidence: 99%
“…The PGRMC2 protein also exhibited increased phosphorylation in the MA-10 Leydig cells treated with Fsk+AICAR vs. controls. PGRMC2 is a membrane-associated progesterone receptor (MAPR) present in Leydig cells and is believed to play a role in the progesterone auto/paracrine action on Leydig cells [ 55 , 56 ] in addition to potentially regulating the activity of some cytochrome P450 enzymes [ 57 ]. We showed that PGRMC2 is present in MA-10 Leydig cells and that it is phosphorylated after AMPK activation.…”
Section: Discussionmentioning
confidence: 99%
“…Rahman and colleagues showed that mifepristone also influences PGRMC1 signaling. For ovarian [38] and testicular [39] cancer models mifepristone leads to PGRMC1 translocation to the nucleus which is associated with altered gene expression, increased proliferation, migration, and invasiveness in mouse xenograft tumor models. PGRMC1 post-translational modifications were not examined, but Sabbir's findings would predict that mifepristone affects particularly PGRMC1's phosphorylation and sumoylation states.…”
Section: Pgrmc1 and Diabetesmentioning
confidence: 99%
“…However, PGRMC1's role in tumor development and progression is not limited to breast cancer. Indeed, several studies reported its involvement also in other hormone-sensitive cancers, including testicular Leydig cell tumor proliferation and invasion through Transforming Growth Factor beta (TGF-β) alternative pathway [169], endometrial cancer [170] and ovarian cancer, in which PGRMC1 activation promotes cell viability, growth, proliferation, migration and survival through PI3K/Akt-mediated inhibition of apoptosis [171,172] (Figure 4). PGRMC2 is a membrane-bound receptor structurally similar to PGRMC1, although it displays a different N-terminal transmembrane domain and is less functionally characterized [173].…”
Section: Maprsmentioning
confidence: 99%